Practical Media / A Guide to Production Techniques - Dimbleby Nick; Dimbleby Richard; Whittington Ken (Hodder & Stoughton, 1994)
A clear, easy-to-use text that shows you how to plan and make audio/ visual productions in a variety of media. Preface, Creating Audio-Visual Productions, Photography, Audio and Radio Techniques, Slide/ Tape Productions, Video and Television Production, Desktop Publishing and Basic Graphic Design and Multimedia, Activities, Resources, Index.